Perancangan Sistem Informasi Perpustakaan Berbasis Web SMK Negeri 3 Karawang - Mulyani Yani (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
The school library is a school facility that manages the provision of textbooks and reference books for general science, technology and other applied sciences. Libraries play a very important role in helping students meet their needs for books and references in an easy and cost-effective way. However, in practice, until now there are still many management obstacles, such as managing inventory levels, the number of borrowers, calculating the amount of repayments, and registering loans. The Library of SMK Negeri 3 Karawang is still managed manually, data collection is not well documented and service is not optimal so that it can lead to errors in borrowing and returning existing books. The purpose of this research is to solve the above problems by designing a web-based library information system. This system can make loans online, manage book inventory, create lists of borrowers, generate return lists, and generate reports. This web-based library information system development method uses a descriptive method using the MySQL database PHP programming language. After designing and testing this application, you can help improve library management and improve library management services at SMK Negeri 3 Karawang.